Infant and Child Mortality "Problematic of terms, and Mechanisms of Determinant's Adjustment" (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Infant and child mortality is considered as one of the most sensitive demographic indicators that reflect the levels of economic and social development and the success of the development process in any given society. Although there are many researches and studies that treat this subject, using statistics and data on local, regional, and international levels; yet, its theoretical framing and the adjustment of its terms and concepts remained for long decades a field of construction, reconstruction, and development for many demographers. Moreover, the adjustment of the determinants of infant and child mortality revealed many divergences, as it is affected by a variety of very complicated economic, demographic, social, cultural, behavioral, and even political and security factors. This makes the problematic of the conceptual and theoretical framing of the study of infant and child mortality an essential step in the construction of applied researches in this field. This study aims to represent the keys for this conceptual and theoretical framing, by treating firstly the conceptual problematics concerning the subdivision of infant and child mortality in its diversity and differences, and by trying secondly to condense the intermediate and the socioeconomic determinants that affect this phenomenon, and might direct the work of applied researches in this field, and develop the analytic and comparative analyzes of their results.